Analisis Geokimia Unsur Penyusun Batugamping di Daerah Iluta dan Sekitarnya, Kecamatan Batudaa, Provinsi Gorontalo - Hamimu, Moh Febrianto; Zainuri, Ahmad; Kasim, Muh (Universitas Negeri Gorontalo, 2025)
This study was conducted in Iluta Village, Batudaa District, Gorontalo Regency, to determine thepetrographic characteristics, geochemical composition, and potential utilization of limestone. The research methods included geological mapping, rock sampling, petrographic analysis using thin sections, and geochemical analysis through X-Ray Fluorescence (XRF). The stratigraphy of the study area consists of limestone units with packstone, wackstone, and mudstone facies, as well as alluvial deposits. Petrographic observations show that packstone is dominated by micrite (73%), vuggy pores (16%), and foraminifera (11%); wackstone by vuggy pores (42%), micrite (34%), foraminifera (13%), and calcite (11%); while mudstone contains calcite (52%), micrite (40%), and foraminifera (8%). Geochemical results indicate that samples FH4 and FH18 have high CaO (±49– 50%) and low SiO₂–Al₂O₃, suggesting high-quality limestone suitable for cement and quicklime production. Conversely, sample FH22, with high SiO₂–Al₂O₃ and low CaO (±8.31%), represents silicate-rich mudstone unsuitable for industrial limestone use.